Origin, distribution and systematics of culinary cucumber (Cucumis melo subsp. agrestis var. conomon) - K R M Swamy (Journal of Horticultural Sciences, 2017)
The non-dessert or culinary forms of C. melo are a distinct group distributed and adapted well essentially under humid tropics of Southern India. Culinary cucumber or vegetable cucumber (Cucumis melo subsp. agrestis var. conomon) belongs to the family Cucurbitaceae, genus Cucumis, species melo, subspecies agrestis and variety conomon. In English, it is popularly called as Mangaluru cucumber, Oriental pickling melon, Japanese pickling melon, golden melon, culinary melon, Indian yellow cucumber, yellow cucumber, lemon cucumber, and so on. Although much of the information about culinary cucumber calls them cucumbers they are not cucumbers! They are actually a part of the so called “conomon” group of melons (Cucumis melo). Traditionally the conomon melons have been used in the Far East for pickling. Culinary cucumbers have a special feature that the fruits can be stored up to 8-10 months without losing their freshness. They can be stored for many weeks by hanging them from the ceiling, firmly bound by thin coconut fibre ropes. This ethnic vegetable is used for preparation of various culinary items. Even seeds are used for preparation of juice against dyspepsia. In this review article, the aspects about the family to which culinary cucumber belongs, genus Cucumis, origin and distribution of the genus Cucumis, domestication of melons (Cucumis melo), intraspecific classification of Cucumis melo, genetic diversity in melons, crossability among Cucumis species, and among Cucumis melo subspecies, origin and distribution of culinary cucumber, uses, nutritional value, medicinal properties, evaluation of germplasm, high yielding varieties, cultivation aspects, have been discussed. Understanding the evolutionary history and domestication process, increases the possibility for better exploiting the genetic diversity for cultivar development. Its storage trait can be transferred to muskmelon by adopting a suitable breeding method. The local landraces or varieties which are highly tolerant to high temperature, drought, pests and diseases in summer, can also be employed as a useful breeding material.